Interest parity at short and long horizons - Menzie David Chinn; Guy Meredith (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The unbiasedness hypothesis
urn:nbn:de:kobv:11-10047563
Keywords: F21; F31; F41; 330; the joint hypothesis of uncovered interest parity (UIP) and rational expectations